0135 Signs of Expiratory Airflow Obstruction In Mouse Model Of Pharyngeal Collapsibility. (27th April 2018) - Nishimura, Y; Arias, R S; Curado, T F; Pho, H; Polotsky, V Y; Suzuki, M; Schwartz, A R
Abstract: Introduction: Investigators have developed laborious procedures for assessing upper airway obstruction during sleep with pressure-area and pressure-flow relationships during drug-induced sleep endoscopy (DISE). During DISE, dynamic changes in pharyngeal patency have been demonstrated throughout the respiratory cycle. We explored streamlined methods for assessing pharyngeal mechanics during expiration, when pharyngeal neuromuscular activity becomes quiescent. Specifically, we compared markers of expiratory airflow obstruction to gold standard measurements of pharyngeal collapsibility in mice. Methods: Four anesthetized mice were instrumented to monitor upper airway pressure-flow relationships with tidal airflow and nasal and tracheal pressure while progressive degrees of pharyngeal obstruction were induced by decreasing nasal pressure in ramp-like fashion over a series of breaths. As nasal pressure decreased progressively, expiratory tracheal pressures paralleled the decreases in nasal pressure initially until nasal pressure fell below a critical pressure (Pcrit), at which point the expiratory nasal and tracheal pressures diverged. Expiratory airflow was profiled during nasal pressure ramps to assess for signs of airflow obstruction including (1) persistent airflow throughout expiration, (2) decreases in peak expiratory airflow, and (3) a sudden jet of flow at end-expiration (expiratory 'pop-off' coinciding with a rise in phasic inspiratory genioglossus activity). Results: The mouse airway occluded at an expiratory Pcrit of -1.85 ± 0.59 cmH₂O, but did not occlude during inspiration. Following the development of expiratory airway occlusion (when nasal pressure fell below Pcrit), progressive decreases in nasal pressure were associated with persistent expiratory airflow, followed by reductions in peak expiratory flow and finally by a sudden expiratory pop-off just prior to the onset of inspiration. Conclusion: Mice exhibit expiratory airflow obstruction with occlusion at a minimally negative critical pressures, suggesting that they can be used to model the impact of key bony and soft tissue factors that predispose to upper airway obstruction during sleep. Our findings also suggest the expiratory airflow profile can complement DISE with quantitative measures of pharyngeal obstruction. Support (If Any): R01HL128970, R01HL133100, R01HL138932.